ANALISIS PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Laksana Baru Swalayan Majenang) - Meilano, Muhammad Reza Anugrah; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2017)
High rate of turnover leads to adverse effect to an organization. Such problem is likely generating instability and uncertainty towards employment condition and human resources cost rise in forms of training invested to them, recruitment and newly built training programs. High turnover, in addition, also results in organizational ineffectiveness because it loses experienced employees as well as spends much times in Â new training, inexperienced employees..This research aim to examine and analyze the influence of the relation between work environment and compensation on turnover intention with job satisfaction as intervening variable (study on employees of Laksana Baru Swalayan Majenang).Questionnaires were distributed to 73 employees of Laksana Baru Swalayan Majenang and data was collected using puposive sampling method. This research used software SPSS Statistic 23.The result of this research indicates that work environment an compensation has positive effect and significant on job satisfaction. Work environment and compensation has negative effect and significant on turnover intention. Job satisfaction has negative effect but not significant on turnover intention,Â sobel test indicates that job satisfaction hasnâ€™t mediation effect on work environment and compensation on turnover intention.